The Reproductive Rights Counteroffensive in Mexico and Central American - Arguedas Ramírez, Gabriela (2017)
This essay reviews the 2013 Human Life International (HLI) propaganda video, Central America and Mexico: Fighting for Life, Faith, and Family, which, we argue, illustrates the well-orchestrated counteroffensive against reproductive and sexual rights movements occurring in the region. First we summarize the film's key themes, including the assertion that Catholicism is fundamental to Mexican and Central American identities and that the international “pro-abortion movement” is waging war against Catholics. Second, we note the development of a new strategic alliance between Catholics and evangelicals that relies on lay religious activists working in the fields of medicine, bioethics, law, and government. Third, we show how the video appeals to HLI donors by asking them to support crisis pregnancy centres, homes for unwed mothers, adoption programs, and “natural” fertility assistance. We argue that the film conspicuously ignores the consequences of abortion bans already in place in Nicaragua, El Salvador, and Honduras, and does not consider that what it terms “international pressures” also includes treaty obligations with the United Nations and Organization of American States. This essay offers insights into the strategies used by opponents of reproductive and sexual rights movements in Mexico and Central America.